Affinity Purification of an Archaeal DNA Replication Protein Network - Zhuo Li (American Society for Microbiology, 2010)
ABSTRACT Nineteen Thermococcus kodakarensis strains have been constructed, each of which synthesizes a different His6-tagged protein known or predicted to be a component of the archaeal DNA replication machinery. Using the His6-tagged proteins, stable complexes assembled in vivo have been isolated directly from clarified cell lysates and the T. kodakarensis proteins present have been identified by mass spectrometry. Based on the results obtained, a network of interactions among the archaeal replication proteins has been established that confirms previously documented and predicted interactions, provides experimental evidence for previously unrecognized interactions between proteins with known functions and with unknown functions, and establishes a firm experimental foundation for archaeal replication research. The proteins identified and their participation in archaeal DNA replication are discussed and related to their bacterial and eukaryotic counterparts. IMPORTANCE DNA replication is a central and essential event in all cell cycles. Historically, the biological world was divided into prokaryotes and eukaryotes, based on the absence or presence of a nuclear membrane, and many components of the DNA replication machinery have been identified and characterized as conserved or nonconserved in prokaryotic versus eukaryotic organisms. However, it is now known that there are two evolutionarily distinct prokaryotic domains, Bacteria and Archaea, and to date, most prokaryotic replication research has investigated bacterial replication. Here, we have taken advantage of recently developed genetic techniques to isolate and identify many proteins likely to be components of the archaeal DNA replication machinery. The results confirm and extend predictions from genome sequencing that the archaeal replication system is less complex but more closely related to a eukaryotic than to a bacterial replication system.